2022
DOI: 10.3389/fimmu.2022.868786
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics Regulates Antitumor Immunity in Melanoma

Abstract: Melanoma is the most malignant skin cancer, which originates from epidermal melanocytes, with increasing worldwide incidence. The escape of immune surveillance is a hallmark of the tumor, which is manifested by the imbalance between the enhanced immune evasion of tumor cells and the impaired antitumor capacity of infiltrating immune cells. According to this notion, the invigoration of the exhausted immune cells by immune checkpoint blockades has gained encouraging outcomes in eliminating tumor cells and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…The patients with CMM are often diagnosed as advanced stage due to the inadequate attention, which is explained as one of the reasons for its poor prognosis and high mortality [ 19 ]. So due to the unsatisfaction of relatively poor diagnosis and prognosis of CMM, numerous studies on association between the related factors and the treatment of CMM have been receiving increasing attention [ 20 , 21 ]. Therefore, searching for these novel treatments are of great significance for CMM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients with CMM are often diagnosed as advanced stage due to the inadequate attention, which is explained as one of the reasons for its poor prognosis and high mortality [ 19 ]. So due to the unsatisfaction of relatively poor diagnosis and prognosis of CMM, numerous studies on association between the related factors and the treatment of CMM have been receiving increasing attention [ 20 , 21 ]. Therefore, searching for these novel treatments are of great significance for CMM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, searching for these novel treatments are of great significance for CMM. There is growing evidence that lncRNAs play a broad regulatory role as active biomolecules in the carcinogenesis and progression of CMM [ 14 , 15 , 20 ]. Depending on the location, lncRNAs can achieve their functions by being implicated in the production and progression of target genes on various levels [ 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serrano et al demonstrated that hypermethylation of HLA-A and HLA-B genes in tumor cells can switch off HLA class genes and enable melanoma cells to escape immune surveillance and recognition. Treatment with a demethylating agent 5'-aza-2'-deoxycytidine (DAC) allows HLA-A and HLA-B transcription can restore tumor cell recognition by cytotoxic T lymphocytes (CTL) [58][59][60][61].…”
Section: Aberrant Dna Methylationmentioning
confidence: 99%
“…Encouragingly, this combinatorial approach proved safe and well-tolerated, demonstrating favorable immunomodulatory and antitumor activity [75]. Equally noteworthy are ongoing trials investigating the synergy between epigenetic agents and immunotherapy in the context of melanoma [59]. In the vein of HDAC6, its role in regulating PD-L1 expression in melanoma by activating STAT3, thereby impacting the growth and progression of melanoma, has been underscored.…”
Section: Immunotherapy and Epigeneticsmentioning
confidence: 99%
“…On the other hand, there is increasing evidence that melanoma pathogenesis is also associated with specific aberrant epigenetic modifications, leading to drug-acquired resistance, evasion of the immune system, apoptosis, and increased metastatic potential. Thus, the reversal of an abnormal epigenetic landscape appears to be a promising therapeutic approach, such as in the case of EZH2 (Enhancer of Zeste Homologue 2; a histone methyltransferase) over-expression and its role in melanoma development and progression [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%